Honour and Shame as Moral-Emotional Identity Regulation in Diaspora: An Interpretative Phenomenological Analysis of Young British South Asian Women - Samrah, Asif; Aman, Asif-Malik (Journal of Human Psychology, 2026)
Honour and shame are central moral constructs within many South Asian communities, yet their psychological internalisation in diasporic contexts remains underexamined. This qualitative study explored how young British South Asian women (aged 18–25; N = 6) understand and negotiate honour in relation to gender, religion, and identity. Semi-structured interviews were analysed using Interpretative Phenomenological Analysis. Six interrelated themes illustrated honour as a gendered and relational system sustained through anticipatory shame, behavioural surveillance, and sexual double standards. Participants described internalised self-monitoring, bicultural identity tension, and strategic resistance through selective compliance and religious reinterpretation. We propose that honour and shame in minority diaspora contexts function as a moral-emotional identity-regulation system characterised by anticipatory shame, relational accountability, and boundary maintenance under racialisation. This conceptualisation advances acculturation and bicultural identity frameworks by arguing that moral emotion, particularly anticipatory shame, functions as a primary mechanism of cultural internalisation, rather than merely an outcome of value endorsement. The findings further illuminate how moral surveillance shapes identity negotiation and psychological wellbeing, with implications for culturally responsive community and clinical practice.
Keywords: honour; shame; diaspora; bicultural identity; gender; community psychology